Learning Informatica PowerCenter 9.x : learn the art of extracting data from disparate systems, integrating it using the leading data integration platform, and creating intelligent data centers for your business /: learn the art of extracting data from disparate systems, integrating it using the leading data integration platform, and creating intelligent data centers for your business. (2014) - Malewar, Rahul
No abstract available